METHOD FOR PLANE NEAR-FIELD ACOUSTIC HOLOGRAPHY BASED ON COMPRESSIVE SAMPLING AND ITS APPLICATION - DU Bao; LUO Jian; HU Fei; LIU XiaoQin; WU Xing (Jixie qiangdu, 2016)
In traditional plane near-field acoustic holography reconstruction process,regardless of wave number domain filter or regularization method,they cannot solve their own ill-posed problem,and thus cannot improve the reconstruction accuracy. Plane near-field acoustic holography based on Compressive Sampling,translates traditional solved particle velocity into solving sparse coefficient,by effective using of the particle velocity sparsity,avoiding the reconstruction process of ill-posed problem. Combined with plane near-field acoustic holography based on Tikhonov regularization method, we analyze the reconstruction accuracy of numerical simulation. The results show that, plane near-field acoustic holography based on Compressive Sampling has a good accuracy in reconstruction process,especially in the border region of reconstructive surface.Finally,this method can effectively identify the source of the noise of the refrigerator,to provide an effective basis for noise control.